1991
DOI: 10.1128/iai.59.1.337-345.1991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bordetella pertussis infection on human respiratory epithelium in vivo and in vitro

Abstract: Bordetella pertussis infection probably involves attachment to and destruction of ciliated epithelial cells, but most previous studies have used animal tissue. During an epidemic, nasal epithelial biopsy specimens of 15 children (aged 1 month to 3 1/2 years) with whooping cough were examined for ciliary beat frequency, percent ciliation of the epithelium, and ciliary and epithelial cell ultrastructure. In addition, the in vitro effects of filtrates from a 24-h broth culture and of tracheal cytotoxin derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
0
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 22 publications
4
19
0
3
Order By: Relevance
“…Since we observed no effect on the viability of the cells, we conclude that neither virulence factor has a toxic effect on respiratory tract epithelial cells. This observation is supported by an earlier report describing that tracheal cytotoxin instead of PT is the toxic virulence factor for primary human ciliated bronchial epithelium (52).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Since we observed no effect on the viability of the cells, we conclude that neither virulence factor has a toxic effect on respiratory tract epithelial cells. This observation is supported by an earlier report describing that tracheal cytotoxin instead of PT is the toxic virulence factor for primary human ciliated bronchial epithelium (52).…”
Section: Discussionsupporting
confidence: 84%
“…Some of these factors, including pertussis toxin (PT), adenylate cyclase, tracheal cytotoxin, dermonecrotic toxin, and lipopolysaccharide, exert a toxic effect. Other virulence factors, such as filamentous hemagglutinin (FHA), fimbriae, pertactin (Prn), and PT, have been reported to mediate the adherence of B. pertussis to various mammalian cells, including human epithelial cells (11,14,47,49,52) and human monocytes (17,36). However, most of these studies pertain to the role of one or more of these virulence factors in the binding of B. pertussis to cells (4,12,13,28,32,38,47,49,51); a comparative study of the most relevant adhesion factors was lacking until now.…”
mentioning
confidence: 99%
“…TCT cytotoxicity has been previously documented in both hamster tracheal (6) and human nasal (28) organ cultures incubated with 10-6 M TCT. We have shown that TCT at 10-11 M is able to significantly inhibit important human neutrophil functions in vitro, and TCT is thus more potent in this biological assay system than in those previously described (6,28). The concentrations of TCT present in the airways of patients infected with B. pertiussis are not known, although in vitro studies have shown that under optimal conditions, 10-6 M TCT may be elaborated in broth culture (6).…”
Section: Discussionmentioning
confidence: 82%
“…1999), although, for the latter, host cell death was contact dependent as EPEC is a non‐invasive pathogen. Bordetella pertussis infection increased the number of dead respiratory epithelial cells in vitro progressively and dose dependently (Wilson et al . 1991).…”
Section: Discussionmentioning
confidence: 99%